Uma investigação experimental da possível aversividade do S- em uma discriminação com ratos - Possmoser, Thalita Lima (2018)
Verifying whether escape responses to the S-, the present stimulus in the extinction condition, may be installed in that condition is a manner by which behavior analysts have been studying the possible averseness of the S-. In general, such studies have been using pigeons. This study aimed to verify whether responses that eliminate the S- might be installed and maintained in four water-deprived rats for whom water was used as reinforcer. The subjects passed through five experimental phases: (1) lever-press response shaping on a right lever, the only one available in this phase; (2) lever-press response strengthening, and a tone was present throughout the sessions; (3) introduction of FR 3 schedule of reinforcement to the lever-press response; (4) setout of discrimination between tone (S+) and light (S-) and introduction of a left lever that, when pressed throughout the S-, ceased the stimulus for 5 seconds; (5) discrimination still in effect and lever-press responses on the left lever in extinction (they did not cease the S- anymore). It was observed that the lever-press responses on the left lever during the S- were mostly emitted in the beginning of the discriminative training. For two subjects, there was a low number of those responses, which ceased of being emitted before Phase 5 (extinction). For other two subjects, there was a higher number of those responses, and, for one of those subjects, the responses remained elevated during the entire discriminative training. The found results do not allow affirming unequivocally whether the S- became aversive or not